PENGARUH RASIO SOLVABILITAS DAN RASIO PROFITABILITAS TERHADAP PENGHINDARAN PAJAK - Nabilla Aulia Qoirunisa; Yulyanah Yulyanah (CV. Denasya Smart Publisher, 2025)
This study aims to investigate how solvency and profitability ratios influence tax avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The solvency ratio is represented by the Debt to Asset Ratio (DAR), while the profitability ratio is represented by the Return on Assets (ROA), and Tax avoidance is measured using the Effective Tax Rate (ETR). The study sample includes 17 companies, determined through purposive sampling, with annual financial reports obtained from the official IDX portal. The data were analyzed using multiple linear regression with the help of E-Views 13 software. The findings reveal that the solvency ratio does not significantly affect tax avoidance, whereas the profitability ratio shows a significant negative effect, indicating that higher profitability is associated with a reduced tendency toward tax avoidance.